THREE-LEVEL DIRECT TORQUE CONTROL BASED ON COMMON MODE VOLTAGE REDUCTION STRATEGY FED TWO PARALLEL CONNECTED FIVE-PHASE INDUCTION MACHINE (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2024)
This survey proposes a mitigation approach for common mode voltage produced in a three-level five-phase inverter fed two parallel-connected five-phase induction machines controlled by direct torque control. The switching frequencies used in the inverter fed these types of drives are characterized by a large amplitude of the produced common mode voltage waveforms (), leading to prominent issues, especially with the near introduction of wide-gap semiconductor technologies. In this context, the introduced approach is an extension to a multi-motor drive of the TATTE method, exploiting the concept of virtual voltage vectors to mitigate the resulting common mode voltage. The collected results critically evaluate the reported approach by improving the drive’s generated common mode voltage status to () compared to () in the conventional method, in addition to a significant reduction in the flux and torque ripples by 22 % and 39 %, respectively, at the cost of an insignificant increase in the current harmonic content by 6 %.
Keywords: Common mode voltage (CMV); Direct torque control (DTC); Parallel connected drive; Five-phase induction machine (FPIM); Five-phase three-level inverter